ENHANCING ESP TEACHING FOR COMPUTER AND NETWORK ENGINEERING STUDENTS THROUGH MULTIMEDIA - Latifah, Fatimatul; Hartiningsih, Sri; Yawisah, Umi; Sabilah, Fardini (University of Kuningan, 2024)
This article discusses the application of short videos and pictures in teaching ESP procedure texts in computer and network engineering majors. This research uses a qualitative method with a case study design to explore the integration of video and pictures in ESP teaching, the challenges teachers face in integrating videos and pictures in ESP teaching, and how teachers overcome these challenges. The participants of this study consisted of one English teacher in computer and network engineering class who was selected by purposive sampling. The research was conducted at SMK Mahardika Malang and involved English teachers from the computer and network engineering department. Data collection methods included observation and interviews with teachers, focusing on the procedures for integrating short videos and pictures, the challenges faced, and solutions to overcome these challenges. The findings reveal that there are several activities in the classroom, namely teacher activities, student activities, and the learning and teaching process. Teachers face three challenges. The first is time constraints. To overcome this challenge, teachers must use pictures and short videos wisely and adjust them to the time available in the lesson plan. The second is the mismatch of learning material sources. The solution to this challenge is to use effective multimedia such as the Internet and YouTube. The third is students' low motivation to learn English and write procedural texts. The solution to this challenge is for teachers to approach students emotionally, consult with their parents, and provide project-based learning strategies using English. This research provides valuable insights for ESP education, emphasizing the importance of adapting content to industry needs, addressing motivation issues, and effectively using multimedia elements.